2014
DOI: 10.1534/genetics.114.170423
|View full text |Cite
|
Sign up to set email alerts
|

Scalable and Versatile Genome Editing Using Linear DNAs with Microhomology to Cas9 Sites inCaenorhabditis elegans

Abstract: Homology-directed repair (HDR) of double-strand DNA breaks is a promising method for genome editing, but is thought to be less efficient than error-prone nonhomologous end joining in most cell types. We have investigated HDR of double-strand breaks induced by CRISPR-associated protein 9 (Cas9) in Caenorhabditis elegans. We find that HDR is very robust in the C. elegans germline. Linear repair templates with short (∼30–60 bases) homology arms support the integration of base and gene-sized edits with high effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
358
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 308 publications
(372 citation statements)
references
References 26 publications
14
358
0
Order By: Relevance
“…Our efforts at Cas9-directed editing succeeded with all 39 GG guides. In contrast, success was infrequent and unpredictable with guides lacking a 39 GG in our study and in published studies (Table S1) (Chiu et al 2013;Cho et al 2013;Dickinson et al 2013;Friedland et al 2013;Katic and Grosshans 2013;Lo et al 2013;Tzur et al 2013;Liu et al 2014;Paix et al 2014;Shen et al 2014;Waaijers and Boxem 2014;Zhao et al 2014). We also found that a 39 GG dinucleotide reliably increased the frequency of genome editing at all targets, even related targets for which the 39 GG-shift guides supported a low to modest frequency of editing.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Our efforts at Cas9-directed editing succeeded with all 39 GG guides. In contrast, success was infrequent and unpredictable with guides lacking a 39 GG in our study and in published studies (Table S1) (Chiu et al 2013;Cho et al 2013;Dickinson et al 2013;Friedland et al 2013;Katic and Grosshans 2013;Lo et al 2013;Tzur et al 2013;Liu et al 2014;Paix et al 2014;Shen et al 2014;Waaijers and Boxem 2014;Zhao et al 2014). We also found that a 39 GG dinucleotide reliably increased the frequency of genome editing at all targets, even related targets for which the 39 GG-shift guides supported a low to modest frequency of editing.…”
supporting
confidence: 56%
“…The initial report describing the successful use of Cas9 in C. elegans demonstrated a range of editing frequencies from 0.5 to 80%, with only two targets exceeding 4% . Subsequent publications also reported variably low mutagenesis rates that required molecular screening of hundreds of animals or required the desired mutation to cause an easily detectable mutant phenotype or to be introduced in tandem with a coselection marker (Chiu et al 2013;Cho et al 2013;Dickinson et al 2013;Katic and Grosshans 2013;Lo et al 2013;Tzur et al 2013;Waaijers et al 2013;Chen et al 2014;Liu et al 2014;Paix et al 2014;Shen et al 2014;Zhao et al 2014). More recent studies greatly improved the odds of detecting a targeted mutation through the simultaneous co-conversion of a mutation in an unrelated target that causes a visible phenotype (Arribere et al 2014;Kim et al 2014;Ward 2014).…”
mentioning
confidence: 99%
“…Short homology arms of just 30-60 bp were pioneered for co-CRISPR applications by the Seydoux group (Paix et al 2014). We have similarly observed that homology arms of just 57 bp generated insertions at high frequency at most loci tested.…”
Section: Discussionmentioning
confidence: 70%
“…In previous studies, homology arms as short as 500 bp for plasmid repair templates and 30 bp for linear repair templates efficiently direct insertion into the C. elegans genome (Paix et al 2014;Dickinson et al 2015). To determine the effect of homology arm length on insertion frequency for SapTrap vectors, we targeted the 59 end of the snb-1 gene with a gfp cassette flanked by homology arms 0, 44, 100, or 400 bp in length ( Figure 3A and Table S3).…”
Section: Short Homology Armsmentioning
confidence: 99%
“…Recently, a CRISPR allele of nos-2 has also been created. 21 Both nos-2 mutations confer only a minor sterility on their own, in contrast to reports of nos-2 (RNAi). 8 Since nos-2(RNAi) should also knock down expression of the T02G5.11, it remains possible that this predicted pseudogene retains some ancestral function.…”
Section: Nanos Family Members In C Elegansmentioning
confidence: 82%